Risk factors of quality of life among tuberculosis patients - Liena Sofiana; Suci Musvita Ayu; Yuniar Wardani; Evelyn Puspaningrum; Dinda Dwi Hadianti (Intelektual Pustaka Media Utama, 2022)
Indonesia has the world's third highest tuberculosis (TB) burden. As a result, Indonesia continues to face TB control issues, accounting for 8% of all tuberculosis cases worldwide. The case results were made in 2018 and discovered 1,016 persons with positive smear as many as 436 TB illness can have an influence on patients' quality of life. The goal of this study was to determine the risk factors of TB patients' quality of life in Sleman Regency, Special Region of Yogyakarta, Indonesia. This research is a cross-sectional analytic observational study. Respondents were the 2nd trimester tuberculosis patients who were still receiving treatment at all Puskesmas in Sleman Regency, Yogyakarta Special Region, Indonesia in 2020. Purposive sampling was used during the sample process. The WHO quality of life (WHOQOL-BREF) questionnaire was used to assess quality of life, while the Morisky Medication Adherence Scale was used to assess knowledge, self-efficacy, family support, and medication adherence. The Chi-square test was used to analyze the data. Self-efficacy (sig=0.013; RP=2.295) and medication adherence (sig=0.014; RP=8.333) were linked to TB patients' quality of life. Knowledge (sig=0.384; RP=0.709) and family support (sig=0.227; RP=0.419) were not connected to TB patients' quality of life. In the Sleman Regency, Yogyakarta Special Region, self-efficacy and medication adherence are risk factors for quality of life among TB patients.